P686Abnormal electrical activity of remodelled T-tubules promotes asynchronous Ca2+ release in heart failure. (15th July 2014) - Crocini, C; Coppini, R; Ferrantini, C; Yan, P; Loew, L; Tesi, C; Poggesi, C; Cerbai, E; Pavone, F S; Sacconi, L
Abstract: Action potential (AP), via the transverse axial tubular system (TATS), synchronously triggers uniform Ca2+-release throughout the cardiomyocyte. Cardiac diseases associated with TATS structural remodeling preclude a uniform Ca2+-release across the myocyte, contributing to contractile dysfunction. Here, we combined the advantage of an ultrafast random access multi-photon (RAMP) microscope with a double staining approach to optically record AP in several TATS elements and, simultaneously, the corresponding local Ca2+-transient. In rat control cardiomyocytes, although AP was uniform between surface sarcolemma (SS) and t-tubules (TT) at steady-state stimulation, we observed a non-negligible beat-to-beat variability of local Ca2+-transient amplitude and kinetics. This variability was significantly reduced applying 0.1 μM Isoproterenol, which increases the open probability of Ca2+-release units. Ca2+ sparks, detected at times throughout the TATS, did not induce any membrane potential variation in the surrounding tubular elements. In a rat model of post-ischemic heart failure (HF), we previously demonstrated that some tubular elements fail to propagate AP (AP-; Sacconi PNAS 2012). Here, we found that those AP- tubules displayed a slower and reduced local Ca2+-transient compared to electrically coupled tubules (AP+). Consistently, in a model of acute detubulation, tubules that do not conduct AP showed a local reduction and delay of Ca2+-transient rise. In addition, variability of Ca2+-transient kinetics was increased in HF. Finally, AP- tubular elements, occasionally exhibited spontaneous depolarisations of various amplitude and kinetics. These events were never accompanied by local Ca2+-release in the absence of pro-arrhythmogenic stimuli, while they could induce local Ca2+-release in the presence of 0.1 μM Isoproterenol. Simultaneous recording of AP and Ca2+-transient allows us to probe the spatio-temporal variability of Ca2+-release, whereas the investigation of Ca2+-transient in HF discloses an unexpected uncoupling between t-tubular depolarization and Ca2+-release in remodelled tubules. This work was supported by the European Union 7th Framework Program (FP7/2007- 2013) under grant agreement n° 284464, 241526, by the Italian Ministry of University and Research (NANOMAX), and by Telethon-Italy (GGP13162).